Surface Modification of the EBM Ti-6Al-4V Alloy by Pulsed Ion Beam - Pushilina N. S. Natalia Sergeevna; Stepanova E. N. Ekaterina Nikolaevna; Stepanov A. V. Andrey Vladimirovich; Syrtanov M. S. Maksim Sergeevich (2021, 2021)
Title screen